Cloning and construction of entry vector carrying IL-6 gene from Vietnamese chicken - Thu Huyen, Vu Thi; Kim Cuc, Nguyen Thi; Hong Minh, Le Thi; Kim Dung, Tran Thi; Cuong, Pham Viet (Academia Journal of Biology, 2013)
Cytokines are a diverse family of proteins that play a crucial role in controlling the immune system. They determine both the type and extent of an immune response that is generated following infection with a pathogen or after vaccination. In this paper, chicken IL-6 gene (ChIL-6) was cloned and ligated in a shuttle vector, as basic to construction adenovirus vector for cytokine gene delivery in chicken for improving of their immune responses to pathogens. By PCR technique, using specific primers for chicken IL-6 gen (ChIL-6) possessing recognition sites of restriction enzymes Kpn I and Not I and Kozak sequence, the ChIL-6 was cloned into pCR2.1 vector. The gene in recombinant pCR2.1/ChIL-6 was sequenced, the obtained sequence had 726 nucleotides and was 99% similarly to the sequences in GenBank after BLASTn. The sequence has been reported to GenBank with Accession no JQ897539. For construction pShuttle/ChIL-6 vector, the cloning vector pCR2.1/ChIL-6 and pShuttle were digested by Kpn I and Not I, then the ligation reaction was performed with T4 ligase and transformed E. coli DH5α clones were selected on LB medium supplemented with ampicilin. The presence of ChIL-6 gen in pShuttle vector was verified by digestion of recombinant plasmid with Kpn I and Not I, as well as by PCR. Received results demonstrated that ChIL-6 gen was ligated into pShuttle and gave pShuttle/ChIL-6 vector.